Corporate governance regulation : how poor management is destroying the global economy - Vakkur, Nicholas V.; Herrera, Zulma J. (Hoboken, N.J. : John Wiley & Sons, 2013)
Modern history persuasively demonstrates the inexorable link that binds comprehensive regulation to the global economy. This important book, rather than simply recount a litany of corporate governance failures, persuasively explains why, despite policymakers' best intentions, regulation has failed in the modern era. An objective study intended for a diverse readership, Corporate Governance Regulation unveils the underlying, root causes of regulatory failure.
Cover -- Title Page -- Copyright -- Contents -- Preface -- Introduction -- Chapter 1. Virtue Lost -- Chapter 2. An Introduction to WorldCom -- Chapter 3. The Enactment Process -- Chapter 4. CEO Perception -- Chapter 5. Sarbanes -- Chapter 6. An Audit of Sarbanes-Oxley -- Chapter 7. The Underlying Vision -- Chapter 8. The Argument for Accountability -- Chapter 9. Why Sarbanes-Oxley?
Includes bibliographical references and index.
Keywords: CORPORATE GOVERNANCE